LEGAL PROTECTION OF THE PARTIES IN CREDIT AGREEMENT WITH FIDUCIARY GUARANTEE AFTER THE ISSUENCE OF CONSTITUTIONAL COURT DECISION No. 18/PUU-XVII/2019 - Celina Tri Siwi Kristiyanti (Warmadewa Press, 2021)
Fiduciary Guarantee Law is one of the material guarantees specifically regulated in Law No. 42 of 1999 on Fiduciary Guarantees that realizes the public's need for legal certainty but guaranteed objects still have economic value. Article 15 of Law No. 42 of 1999 concerning Fiduciary Guarantees is felt burdensome to debtors, because creditors make forced efforts to take fiduciary guarantee objects in the form of 2-wheeled and 4-wheeled vehicles. The purpose of this study is (1) Finding and analyzing the basis of the Constitutional Court's Decision No. 18/PUU-XVII/2019 (2) Finding and explaining the legal consequences of the Constitutional Court Decision No. 18/PUU-XVII/2019 on legal protection for parties to credit agreements with fiduciary guarantees (3) Finding and explaining constraints on Financial Service Institutions (LJK) in the implementation of constitutional court decision No. 18/PUU-XVII/2019. The research method used is juridical normative and empirical with a case study approach so that achievements are more comprehensive related to the principle of legal protection for parties in fiduciary guarantees. The result obtained that since the Decision of the Constitutional Court No. 18/PUU-XVII/2019, the executive confiscation cannot be done directly by creditors must go through a court decision. The executorial confiscation in Article 15 of Law Number 42 concerning Fiduciary Guarantee has been contrary to Article 1 (3), Article 27 (1), Article 28D (1), Article 28G (1) and Article 28H (4) of the Constitution of 1945. It takes good faith from the parties so that the implementation of the Constitutional Court Decision No. 18/PUU-XVII/2019 guarantees justice, legal certainty and provides legal protection. An agreement is required in accordance with the principle of freedom of proportionate contract, there is a balance of position between the debtor and the creditor.